477. TEXTBOOK OUTCOMES FOR OESOPHAGECTOMY: AN EVALUATION OF OESOPHAGECTOMY QUALITY PERFORMANCE INDICATORS AT A SINGLE HIGH-VOLUME AUSTRALIAN OESOPHAGOGASTRIC CENTRE. (24th September 2022) - Wu, M; McGregor, R; Scott, J; Smithers, M; Frankel, A; Barbour, A; Thomson, I
Abstract: In 2017 the Dutch Upper-Gastrointestinal Audit Group (DUCA) proposed a ten-item composite measure for a "textbook outcome" after oesophagogastric resection. Utilising this composite measure, studies have shown associations between textbook outcomes and better conditional and overall survival. The aim of our study was to evaluate the applicability of this measure in the setting of an Australian oesophagogastric centre and to ascertain whether textbook outcome was associated with improved survival. Data were obtained by retrospective analysis of a prospectively maintained database of oesophagogastric malignancies at a single oesophagogastric unit from 2013 to 2018. We used the DUCA group definition of textbook outcomes, encompassing resection radicality, resection margins, lymph node clearance, intra- and post-operative complications, length of stay, hospital and intensive care unit re-admissions, and post-operative mortality. Multivariable logistic regression analysis was conducted to assess association between patient factors and textbook outcome. Cox regression analysis was used to assess association between textbook outcome and survival. Post-operative complications were analysed in two separate groups (Clavien-Dindo ≥2 and Clavien-Dindo ≥3). A total of 246 patients were analysed, with 50.8% achieving a textbook outcome when complications were defined as Clavien-Dindo ≥2 and 58.9% when using Clavien-Dindo ≥3. Patients with age <75 or a respiratory co-morbidity were less likely to achieve a textbook outcome. The 30-, 90-day and 1-year mortality rates were 1.6%, 2.4% and 15% respectively. There was no difference in survival between those who did versus those who did not have a textbook outcome when complications were defined as Clavien-Dindo ≥2. There was improved overall survival if complications were defined as Clavien-Dindo ≥3 (HR0.58, p=0.015). Textbook outcome is a new multi-parameter metric that aims to better capture the quality of oesophageal cancer surgery compared to traditional volume-outcome relationships. We have demonstrated that it is applicable in our population, with the percentage of patients having a textbook outcome comparing favourably with published data. In our series, a textbook outcome was associated with improved overall survival when defining complications as Clavien-Dindo ≥3.